Photosensitizers in medicine: Does nanotechnology make a difference?. (2018) - Zarrintaj, Payam; Ahmadi, Zahed; Hosseinnezhad, Mozhgan; Saeb, Mohammad Reza; Laheurte, Pascal; Mozafari, Masoud
Abstract: Human health is one of the challenging issues which have necessitated the accompaniment of various fields of science. Therefore, the diverse multidisciplinary scope of human health has been emerged using miscellaneous materials with specific applications. Photosensitizers are among the unique materials being utilized in medicine, in particular in cancer treatment. Though they have been partially studied for the treatment of cancer diseases, it is still believed that these materials are on the verge of a new era in the near future. Research on nanotechnology is expected to act as a game changer in this field by changing the basic characteristics of currently available photosensitizers. Photodynamic therapy as a non-invasive therapeutic method is one of the important applications of photosensitizers for disease treatment. The adjuvant methods can assist photosensitizers and phototherapy methods in an optimal way for a more efficient therapeutic result. Nano-sized photosensitizers can be synthesized for enhanced efficiency compared to the conventional techniques. Here, the emerging applications of nano-sized photosensitizers have been highlighted for medical research.